Evaluasi Implementasi Program Pendistribusian Zakat “Agam Makmur” Untuk Pemberdayaan Masyarakat Di Kabupaten Agam” - Desmawati Desmawati; Fitri Eriyanti; Zikri Alhadi (JIPAGS (Journal of Indonesian Public Administration and Governance Studies), 2018)
ABSTRACT This study aims to evaluate the implementation of zakat distribution program "Agam Makmur" for community empowerment in Agam District ". The background of this research is because the amount of aid given is insufficient and the number of business people who do not develop as expected in the distribution program of zakat "Agam Makmur". In this research use qualitative research with descriptive method. This research is head of BAZNAS Agam, Program and IT Manager, Finance Manager, Finance Staff, Administration Staff and community beneficiaries of "Agam Makmur" distribution program. Techniques and tools used in data collection in this study using interview techniques, observation and documentation studies. In this study the data were analyzed using analytical techniques as described by Miles and Huberman. The results stated that in the evaluation of zakat distribution program implementation "Agam Makmur" as a whole can not be said to be successful because the monitoring and evaluation of BAZNAS Agam is not implemented, the assistance given in small amount, the aid given is not right target.Keywords: Evaluation policy, distribution program of zakat "Agam Makmur", BAZNAS Agam